2010
DOI: 10.5251/abjna.2010.1.6.1237.1242
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of involvement of women in seed systems in Borno State, North-East Nigeria

Abstract: The study was on the involvement of women in seed systems in Hawul Local Government Area of Borno State, Nigeria. Multistage probability sampling procedure was employed in the selection of the respondents. In the first stage, four (4) districts were selected. In the next stage, one (1) village was randomly selected from each of the selected districts. Subsequently, twenty five (25) respondents were randomly selected from each of the selected villages, which brought the total number of the respondents to one hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
3
3
0
Order By: Relevance
“…That most of the respondents were middle-aged and in their economically active age implies that they still have the energy to meet with the labour demands of agricultural production. This corroborates the assertion of Bawa et al (2010) that agricultural production activities are mostly carried out by the middle-aged people. The middle and older aged people among the respondents could be due to the result of rural-urban migration of the younger aged and/or youth.…”
Section: Discussionsupporting
confidence: 90%
“…That most of the respondents were middle-aged and in their economically active age implies that they still have the energy to meet with the labour demands of agricultural production. This corroborates the assertion of Bawa et al (2010) that agricultural production activities are mostly carried out by the middle-aged people. The middle and older aged people among the respondents could be due to the result of rural-urban migration of the younger aged and/or youth.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to the findings of[14] who reported that women involved in agricultural seed system activities in Borno State, North-East Nigeria, were within the economically productive age range of18-35. [15] reported that active age of 18-35 facilitates the energy demanding labor in agricultural production.…”
supporting
confidence: 89%
“…Literate farmers are expected to be more innovative because of their ability to obtain and comprehend information more quickly and their ability to take more risk. Bawa, Donye and Nuhu (2010).…”
Section: Results and Discussion Socioeconomic Characteristics Of Respondentsmentioning
confidence: 99%